Review and reform of South African health legislation - Harrison, Stephen Geoffrey Davidson (Centre for Law and Society, 2024)
The 27 April 1994 saw the dawning of a new era in which all South Africans became entitled to a common South African citizenship in a sovereign and democratic state. Political transition brought with it the promise of a better life for all citizens of South Africa as apartheid policies and racist legislation were relegated to the annals of history, and as the process of reconstructing a society torn by discrimination, prejudice and inter-racial strife commenced. The South African health care system was not immune to the destructive policies of the past, and has developed in a fragmented and often poorly co-ordinated manner. This has adversely affected the equitability, affordability, accessibility, effectiveness, efficiency and appropriateness of the South African health care system. The new South African government has identified the improvement of health care as a fundamental component of its Reconstruction and Development Programme. In July 1995, the government also unveiled plans to implement a National Health Insurance System, in terms of which all permanent residents of South Africa would be guaranteed access, on equal terms, to all services provided by a publicly funded Primary Health Care System.